Contemporary management of aortic stenosis: surgical aortic valve replacement remains the gold standard. (8th November 2012) - Walther, Thomas; Blumenstein, Johannes; van Linden, Arnaud; Kempfert, Jörg
Abstract : Aortic valve disease is the most frequent acquired heart valve lesion in humans. In western communities, approximately 90% of patients present with aortic stenosis (AS), predominantly of a calcific degenerative aetiology. The remaining approximately 10% of patients predominantly present with aortic valve incompetence.